Genomic analysis reveals different mechanisms of fusidic acid resistance in Staphylococcus aureus from Danish atopic dermatitis patients. (14th December 2017) - Edslev, Sofie Marie; Clausen, Maja-Lisa; Agner, Tove; Stegger, Marc; Andersen, Paal Skytt
Abstract: Background: Staphylococcus aureus skin colonization is common in patients with atopic dermatitis (AD) and is associated with risk of skin infections. AD patients therefore often receive antibiotic treatments, including topical treatment with fusidic acid, which have been associated with resistance development. Objectives: To examine the prevalence of antibiotic resistance in S. aureus isolated from Danish AD patients, with a primary focus on fusidic acid resistance and the genetic mechanisms that underlie it. Methods: One hundred and thirty-eight S. aureus isolates collected from lesional skin ( n  =   54), non-lesional skin ( n  =   27) and anterior nares ( n  =   57) from 71 adult AD patients were included in the study. Isolates were tested for susceptibility to 17 selected antibiotics. S. aureus whole-genome sequences were used to examine the genetic determinants of fusidic acid resistance ( fusA or fusE mutations or carriage of fusB or fusC genes). Results: One hundred and nine isolates (79%) were resistant to at least one of the tested antibiotics, with the most prevalent resistances being to penicillin (55%), fusidic acid (41%) and erythromycin (11%). The primary genetic mechanisms of fusidic acid resistance were carriage of fusC (57%) or mutations in fusA (38%). The most prevalent S. aureus lineage was ST1 (23%). All ST1 isolates carried fusC . Conclusions: S. aureus fusidic acid resistance, caused by either fusA mutations or fusC gene carriage, is a major concern among AD patients. Resistant S. aureus might spread from the patients to the community, indicating the need to reduce the use of fusidic acid in the treatment of AD.